Veteran Kota Padang: Studi Sosial Ekonomi 1982-2018 - Yuni Zulfitri; Azmi Fitrisia (Jurnal Kronologi, 2020)
This article will discussion about the social economy of Veteran of Padang City between year 1983 until year 2018. Because the independence of Indonesia on Ougust, 17, 1945 is struggle of heroes that concist of soldier and Indonesia’s veteran. The research is history research that using historical method. The heurictic proces was collect document, observation and interview. The conclusion of this research is the Indonesia’s veteran had struggle but part of them after independence of Indonesia is not prosperous. There is something wrong. Begin of the year 2012 was good news that the Indonesia’s veteran was gived allowance by goverment. The UU No 15 Tahun 2012 had manage of the action.